Straż Graniczna w aspekcie rozpoznawania i przeciwdziałania zagrożeniom terroryzmem. Specyfika przejść lotniczych na przykładzie Placówki SG we Wrocławiu-Strachowicach - Sareło-Janiak, Beata (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article focuses on the role of the Border Guard with regard to recognising and counteracting terrorist threats, and on the specificity of airport border crossings as exemplified by the Border Guard post in Wrocław-Strachowice. The Border Guard is a uniformed service established to defend the state’s border on land and sea, and to control border traffic in line with national security interests. The Border Guard’s key tasks, defined in the Border Guard Act, include operations aimed at recognising and counteracting terrorist threats. These consist in e.g. preventing illegal border crossing; preventing trafficking of explosives, arms and ammunition, radioactive materials, hazardous chemical agents and dual use items; ensuring security in international aviation; collecting and analysing information about potential terrorist threats; conducting investigative operations to recognise and counteract terrorist threats; collaborating in terrorism prevention with the Internal Security Agency, Foreign Intelligence Agency, Police, Military Counterintelligence Service, Military Intelligence Service and Military Police as well as border guard services of neighbouring countries. It must be noted that after Poland joined the Schengen Area, its airports began to function as external borders.
Keywords: Straż Graniczna; terroryzm; bezpieczeństwo narodowe; bezpieczeństwo międzynarodowe; zagrożenia bezpieczeństwa; lotniska